2006
DOI: 10.1108/09649420610643420
|View full text |Cite
|
Sign up to set email alerts
|

Constructing a professional identity: how young female managers use role models

Abstract: Role models are often identified as important for aspiring managers as they seek insights into how to develop themselves in their careers. There are, however, still few female role models at the top of companies. This project explores how young careerminded women use role models. It draws on previous research into how professionals experimented with their identity projections to become partners in US professional service firms. In-depth interviews with ten young professional women revealed that they actively d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
94
1
3

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 103 publications
(107 citation statements)
references
References 15 publications
9
94
1
3
Order By: Relevance
“…The research also revealed that leaders should be tough and decisive; the image of a male hero leading his men to victory is supported by a plethora of metaphors from the sporting and military arenas. Although in theory (Baecker, 2014), the heroic leadership model centred on personality cult and charisma has been challenged, recent research (Rojo and Esteban, 2003: 245;Singh et al, 2006) suggests that it is still alive in the form of role models, in training materials and everyday organizational discourses (see Baxter, 2010: 26).…”
Section: Lean Inmentioning
confidence: 99%
“…The research also revealed that leaders should be tough and decisive; the image of a male hero leading his men to victory is supported by a plethora of metaphors from the sporting and military arenas. Although in theory (Baecker, 2014), the heroic leadership model centred on personality cult and charisma has been challenged, recent research (Rojo and Esteban, 2003: 245;Singh et al, 2006) suggests that it is still alive in the form of role models, in training materials and everyday organizational discourses (see Baxter, 2010: 26).…”
Section: Lean Inmentioning
confidence: 99%
“…And I though well, I am doing this course aren't I? (student group D) (2,4,6,8) These enhanced feelings of self-salience and efficacy, of study having permeated the identity at a deep integrative level and transformed notions of previous identities, forming a type of escape into a new persona, feature prominently in the literature on working identities (McAdams, 2006;Singh, et al, 2006). As study becomes increasingly integrated into the individual's identity, it becomes less likely that a student will give this up, or risk losing a valuable part of themselves.…”
Section: )mentioning
confidence: 99%
“…They are also subject to hegemonic influences viewed from a critical realist perspective and which indicate the need for the researcher to "move beyond regularities, experiences and events and to study the underlying causal structures that provide ontological depth to identities" (Joseph, 2002;Bhaskar, 1989). To a certain extent, they are learned identities formed from a mix of personal biographies and interactions with communities within their personal and student lives (Lave et al, 1991b;Wenger, 1998), to be viewed as part of a trajectory of intersecting identities that revolve around culture, assumptions, socioeconomic background, gender, and language (Singh et al, 2006). In part they are modeled on others, yet are also uniquely individual (Edwards, 1996;Burke & Reitzes, 1991).…”
Section: Introductionmentioning
confidence: 99%
“…However, such (more dominant) conduct may be perceived as role-crossing, or out-of-role behavior (Oakley, 2000;Singh & Vinnicombe, 2001), and may therefore be considered unfavorable (Hull & Umansky, 1997;Lehman, 1992). Nonetheless, such disadvantages might diminish over time (Singh, Vinnicombe, & James, 2006), as gradually increasing numbers of women are reaching topranking positions in professional services industries, leading to a more balanced distribution of female and male service professionals across the world.…”
Section: Discussionmentioning
confidence: 99%